Pengaruh Citra Destinasi dan Kepuasan Pelanggan Terhadap Niat Perilaku Pada Lembah Tumpang Resort Kabupaten Malang - Naifa, Fairuz Hasna'; Afandi , Yosi (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research used a quantitative approach. The data was collected by distributing questionnaires to 100 respondents from tourists who visited the Tumpang Valley Resort, Malang Regency, offline (directly). The sampling used non-probability sampling with a purposive sampling technique. The data analysis method in this research used multiple linear regression analysis and hypothesis testing. The results of partial hypothesis testing showed that the destination image positively and significantly affects behavioral intentions. Customer satisfaction has a positive and significant effect on behavioral intentions. The results of simultaneous hypothesis testing showed that the destination image and customer satisfaction have a positive and significant impact on behavioral intentions. From the results of this research, it can be concluded that the destination image and customer satisfaction influence the behavioral intentions in Tumpang Valley, Malang Regency